Ethics from the narrow perspective - Machura, Piotr (Folia Philosophica, 2008)
Book review Jacqueline Russ: Contemporary Ethical Thought. Translated by Agnieszka Kuryś. Warsaw: PAX Publishing Institute, 2006.